Till Taxes Keep Us Apart? The Impact of the Marriage Tax on the Marriage Rate - Nadia Myohl (Center for Economic Studies and ifo Institute (CESifo), 2022)
Married couples often face a different tax burden than cohabitating couples with the same income. I study the effect of joint income taxation of married couples on the marriage rate in Switzerland, where tax differentials between married and cohabitating couples vary considerably across cantons. I construct a dataset containing sociodemographic and -economic variables on every individual living in Switzerland, and use household-level information to identify cohabitating couples. Using a simulated instrumental variable approach, I find a negative impact of joint income taxation on the marriage rate for couples married between 2012 and 2019. The effect is driven by households without children and from the lower end of the income distribution.
Keywords: H24; H31; J12; 330; income taxation; marriage penalty; taxation of married couples